Symmetric key infrastructure for authenticated key establishment between resource constrained nodes and powerful devices. Issue 2 (24th January 2011) - Vossaert, Jan; Lapon, Jorn; De Decker, Bart; Naessens, Vincent
Abstract: This paper presents a generic lightweight solution for authentication between powerful devices and resource constrained nodes. The approach is validated through the architectural design of multiple applications in different domains. The paper further discusses variants that might increase the usability of the approach in different settings. More precisely, the solution is tuned for open systems, closed systems and hierarchically structured systems. Further, two use cases are presented in which the open system and closed system approach is applied. Copyright © 2011 John Wiley & Sons, Ltd. Abstract : Many solutions use a purely symmetric key solution to protect data exchange between lightweight devices and more powerful machines. These solutions, however, fail to fulfill the advanced requirements posed in typical RFID scenarios or scenarios where reader devices from multiple organizations (and hence with tailored privileges) require access to specific services from constrained nodes. This paper proposes a security architecture for authentication, access control and secure data transfer between resource constrained devices and powerful stations that tackles these requirements.